2009
DOI: 10.1080/08927010903154724
|View full text |Cite
|
Sign up to set email alerts
|

Reversible anti-settlement activity againstAmphibalanus(=Balanus)amphitrite, Bugula neritina, andHydroides elegansby a nontoxic pharmaceutical compound, mizolastine

Abstract: Mizolastine, an antihistamine pharmaceutical, was found to significantly inhibit larval settlement of the barnacle Amphibalanus (=Balanus) amphitrite, the bryozoan Bugula neritina, and the polychaete Hydroides elegans with EC(50) values of 4.2, 11.2, and 4.1 microg ml(-1), respectively. No toxicity against the larvae of these three species was observed at the concentration range tested during incubations with mizolastine. To determine whether the anti-settlement activity of mizolastine is reversible, recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…Numerous literature have documented different pharmacological compounds that induce or inhibit larval metamorphosis of many marine invertebrates including hydroids, bryozoans, polychaetes, mollusks, barnacles, sea urchins and ascidians. These studies provide valuable information that has application in the fields of biofouling, antifouling and aquaculture (Cooper 1983;Rittschof et al 1992;Martinez et al 1999;Zhao et al 2003;Gapasin and Polohan 2004;García-Lavandeira et al 2005;Yu et al 2007;Zhou et al 2009). In the present investigation, the authors have demonstrated that chemical compounds chlorpromazine, amitriptyline and TEA inhibit larval metamorphosis of the mussel M. galloprovincialis.…”
Section: Discussionsupporting
confidence: 50%
“…Numerous literature have documented different pharmacological compounds that induce or inhibit larval metamorphosis of many marine invertebrates including hydroids, bryozoans, polychaetes, mollusks, barnacles, sea urchins and ascidians. These studies provide valuable information that has application in the fields of biofouling, antifouling and aquaculture (Cooper 1983;Rittschof et al 1992;Martinez et al 1999;Zhao et al 2003;Gapasin and Polohan 2004;García-Lavandeira et al 2005;Yu et al 2007;Zhou et al 2009). In the present investigation, the authors have demonstrated that chemical compounds chlorpromazine, amitriptyline and TEA inhibit larval metamorphosis of the mussel M. galloprovincialis.…”
Section: Discussionsupporting
confidence: 50%
“…It will be important to analyze the concentration of HA in the seawater around such biofilms as well as in algal turf and crustose coralline algae to test their role in the settlement response of sea urchin larvae. This is particularly relevant as HA signaling may be involved in the settlement processes of barnacles, bryozoans and polychaetes as well [65]. Specifically, experiments have shown that a H1R antagonist, mizolastine, has inhibitory effects on the settlement response of selected species from these groups [65].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant as HA signaling may be involved in the settlement processes of barnacles, bryozoans and polychaetes as well [65]. Specifically, experiments have shown that a H1R antagonist, mizolastine, has inhibitory effects on the settlement response of selected species from these groups [65]. Although no further investigations into the signaling mechanisms of HA have been accomplished, these data suggest that HA signaling may be widespread in the marine environment.…”
Section: Discussionmentioning
confidence: 99%
“…The condition of cyprids used in the bioassays for each culture batch was checked by observing mortality and settlement rates. That is, 10 individuals of 3-day-old cyprids were placed in each well of a 12-well polystyrene plate, with each well filled with 4 mL of the filtered seawater, and the number of juveniles that settled and dead cyprids were counted under a dissecting microscope after 48 h [40][41][42].…”
Section: Composition/paint Name A-0 A-1 A-2 A-3 A-4 A-5mentioning
confidence: 99%